EFL College Students' Reading Strategies for Comprehending Reading Texts (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This qualitative study attempts to look into reading strategies employed by college students to comprehend the texts they are reading. Semi-structured interviews and observations were conducted to obtain verbal and nonverbal data regarding reading strategies. The findings revealed that six participants of English students used all types of reading strategies developed by Mokhtari et al.: global reading strategies, problem-solving reading strategies, and support reading strategies. Support reading strategies and problem-solving reading strategies were the most frequent reading strategies the students used, and they seldom applied global reading strategies while reading. However, although they are equally high achiever students, they still need to be better readers; their reading comprehension skills differ.